Biting the hand that feeds you: rebel organisation and one-sided violence in sub-Saharan Africa - Ottmann, Martin (2012)
This thesis examines the relationship between rebel organisation and violence against civilians in sub-Saharan Africa. I argue that rebels use such one-sided violence to enforce popular support when they are unable to secure support otherwise. An important determinant of this strategic use of violence is the rebels' organisational configuration. Organisational factors such as the ideology of a rebel group, the occurrence of leadership divisions, the level of fractionalisation within a rebel group's population base, the existence of external support and the number of competing rebel factions determine whether non-violent strategies to secure support are available or whether rebels can only rely on violent means to enforce support. I test this theoretical model using both quantitative and qualitative methods. First, I conduct a statistical cross-sectional study analysing the relationship between rebel organisation and rebel one-sided violence in sub-Sahara Africa between 1989 and 2007. The analysis reveals that the occurrence of leadership divisions increases the probability of an onset of rebel violence against civilians. I also find that ethno-nationalist rebel groups kill fewer civilians while rebel groups who draw support from highly fractionalised population bases kill more civilians. Second, I use qualitative within-case analyses of the Sudan People's Liberation Movement/Army (SPLM/A) and the Sudan Liberation Movement/Army (SLM/A) to test whether these correlations are actually driven by the causal pathways outlined in my theoretical model. While both case studies provide supporting evidence for this, they also uncover that the causal pathways linking leadership divisions to rebel violence can substantially differ from each other. Moreover, the qualitative analysis reveals that the theoretical model only partly captures the causal pathways between rebel ideology and the rebel groups' population base and the level of one-sided violence.